Positive Learning through Intelligent Media in the Tutoring System Factors - Bekmuratovna, Taylakova Guli (European Journal of Life Safety and Stability (2660-9630), 2021)
The article oversees programming in helper schoolteachers utilize blended media web propels in the classroom effectiveness of usage, positive factors, understudy, educating materials mastering the speed of learning, the size of the material and its difficulties and vanquishing them.